Atrial fibrillation originating from superior vena cava with atrial flutter‐electrocardiogram pattern. Issue 7 (1st June 2017) - Huang, Hung‐Kai; Chang, Shih‐Lin; Lin, Yenn‐Jiang; Lo, Li‐Wei; Hu, Yu‐Feng; Chung, Fa‐Po; Huang, Yen‐Chang; Lin, Chung‐Hsing; Chan, Chao‐Shun; Chang, Hung‐Yu; Lin, Chin‐Yu; Chang, Yao‐Ting; et al.
Abstract: Backgrounds: Substrate property is related to the genesis and maintenance of atrial fibrillation (AF). The aim of the study was to investigate the impact of substrate property on the electrocardiogram (ECG) in patients with AF originating from the superior vena cava (SVC). Methods and Results: Seventy‐six patients with AF originating from SVC who underwent catheter ablation were included from 2004 to 2013. Of these patients, 16 had a presentation of atrial flutter (AFL)‐pattern ECG during AF (group 1), and 60 patients did not (group 2). There was no significant difference in clinical characteristics between the groups. The percentage of low voltage zone (LVZ) in SVC below the level of pulmonary artery in group 1 was significantly larger than that in group 2. The polarities of the flutter wave in 12‐lead ECG were compared with another 26 subjects with reverse typical AFL. The ECG morphology was characterized by negative or biphasic P waves in lead V1 in most of the patients in group 1 (62.5%), which was analogous to that in reverse typical AFL. The negative polarity of flutter waves in aVL might distinguish SVC AF with an AFL‐pattern from reverse typical AFL. Conclusion: The ECG characteristics of AF originating from SVC can mimic atypical AFL. LVZ in the SVC may be associated with the presentation of AFL‐pattern ECG.